Efisiensi Usaha dan Faktor-Faktor Yang Mempengaruhi Produksi Pembenihan Ikan Patin - Anggun Oktaviana; Zulkarnain Zulkarnain; Fikri Syahputra; Kaizan Kaizan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Muhammadiyah Buton, 2023)
Catfish is a freshwater fish in Indonesia which is distributed mostly in Sumatra and Kalimantan. The research was conducted in Metro City with 30 samples used. Sampling technique with census method. The analysis tools are multiple linear regression analysis with the Cobb-Douglas production function, technical efficiency analysis with the Data Envelopment Analisys (DEA) approach, price/allocation efficiency analysis and economic efficiency analysis. The results showed that 1) capital production factors (X2), number of brood stock (X3), and drugs (X9) had a significant effect on the production of catfish hatcheries. 2) technical efficiency value of 0.940. 3) price/allocation efficiency value of 194,098. 4) economic efficiency value of 182,452. Keywords: Economic efficiency, price/allocation efficiency, technical efficiency, catfish